Carceral Citizenship: Race, Rights and Responsibility in the Age of Mass Supervision. (November 2017) - Miller, Reuben Jonathan; Stuart, Forrest
Scholars have shown how formal processes of legal exclusion coupled with ubiquitous criminal justice contact relegate the largely black poor targets of the carceral state to second-class citizenship. Building upon but departing from this work, we reveal how carceral expansion has not just produced new forms of second-class citizenship for poor black Americans, but an alternate citizenship category and a distinct form of political membership—what we call carceral citizenship. The criminal record does this work through a process we call translation, marking the conventional citizen and making them legible, as a carceral citizen, for governance through institutions of coercion and care. We delineate the features of carceral citizenship and discuss its implications for how we understand the role, force, and consequence of the state in the lives of the raced and criminalized poor.